Scatter index measurement using a CT dose profiler - Choirul Anam; Freddy Haryanto; Rena Widita; Idam Arif; Toshioh Fujibuchi; Takatoshi Toyoda; Geoff Dougherty (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2017)
The CT dose index (CTDI) is usually measured using a pencil chamber with a length of 100 mm on a CTDI phantom with a length of 150 mm. The scattering radiation dose beyond 100 mm is usually still significant despite using a small beam width (below 10 mm). This study aims to measure the scattering index of CT dose for several variations of input parameters. The scatter index measurements were performed on a multi-slice CT (MSCT) Alexion™ using a CT dose profiler detector connected to a Black Piranha electrometer (RTI Electronic, Sweden). The measurements used the helical mode and a beam width of 2 x 4 mm, and resulted in 150 mm dose profiles. Values of CTDI150, CTDI130 and CTDI100 were calculated and used to obtain values of the scatter indices (SI130 and SI150). We varied input parameters, such as tube voltage, tube current, and pitch, and used two types of CTDI phantoms, i.e. body and head. In the tube voltage variation (from 80 to 135 kV), we found SI130 and SI150 values of 1.13 ± 0.01 and 1.19 ± 0.01 for the body CTDI phantom; and SI130 and SI150 values of 1.08 ± 0.01 and 1.11 ± 0.01 for the head CTDI phantom. For tube current variations from 25 to 120 mA, and pitch variations from 0.75 to 1.5, SI130 and SI150 values were 1.14 ± 0.00 and 1.20 ± 0.00 for the body CTDI phantom; and 1.08 ± 0.00 and 1.11 ± 0.00 respectively for the head CTDI phantom. We showed that the more frequently used CTDI100 value is too small because it ignores scattering beyond the 100 mm boundary, even for beam widths less than 10 mm. The scatter index values were strongly influenced by the size of the CTDI phantom, and were slightly affected by the tube voltage. Variations in tube currents and pitch did not affect the value of the scatter index. The scatter index values of SI130 and SI150 were significantly different, and suggests that the use of SI150 is even more appropriate for describing the scattering dose.